THE INFLUENCE OF DIRECTED READING THINKING ACTIVITY (DRTA) TOWARDS STUDENTS’ READING ABILITY - Wiratno, Purna (JETA (Journal of English Teaching and Applied Linguistic), 2021)
The research aimed to know the influence of using DRTA Strategy towards students’ reading ability at MTs Nurul Iman Pesawaran. The research was conducted at the eighth grade of MTs Nurul Iman Pesawaran in academic year 2020/2021. The writer took two clasess in the eighth grade as the samples. The population was 40 students’ in 2 clasess. The sample was taken by using cluster random sampling technique. 20 students’ were as experimental class and 20 students’ were as control class. The main technique in measuring students’ reading comprehension was multiple choice test that consisted of 40 test items. The score for each item was 2,5 for true and 0 for wrong. In analyzing the data, the writer used t-test formula. Based on the data analysis, The result showed that t-test was 2.9. From the distribution table at the significance level of 5% is known that t-table = t (1- ½ α) (df) = 2.00 and at the significance level of 1% is known that t-table = t (1- ½ α) (df) = 2.37. It means t-test > t-table as in (2.9> 2.00 > 2.37). Based on the calculation, Ha was accepted, it means that there was an influence of using DRTA (Directed Reading Thinking Activity) strategy towards the students’ reading ability at the eighth grade of MTs Nurul Iman Pesawaran in 2020/2021. Then the average score of students reading ability who learnt through DRTA (Direct Reading Thinking Activity) was higher than those who learnt reading throurgh conventional technique. It was 70.1 > 65.6. Based on the result above, it is clear that DRTA (Directed Reading Thinking Activity) can increase students’ reading ability at the eighth grade of MTs Nurul Iman Pesawaran in 2020/2021.